P3.037 High Prevalence of Genital Warts Among Young Women in Italy. (13th July 2013) - Mariani, L; Salfa, M; Timelli, L; Vittori, G; Fattorini, G; Suligoi, B
Abstract : Background: Worldwide, several million cases of genital warts occur each year. The objective of this study was to estimate the prevalence and the incidence of external genital warts (eGW) in a sample of women attending gynaecological ambulatories and to estimate the number of women with eGW among women aged 15–64 years in Italy. Methods: In 2010, 44 local gynaecologists were included in this prospective study. They reported demographic data for every woman aged 15–64 years that they visited for any reason. For women diagnosed with eGW, behavioural and clinical data were recorded. Prevalence was calculated as the proportion between the number of women with eGW and that of women visited; incidence was calculated as the proportion between the number of women with a new diagnosis of eGW and that of women visited. Standardized prevalence by age was used to estimate the number of eGW cases occurring in Italy in the female population aged 15–64 years. Results: In 2010, 16, 410 women were included; 63 women were diagnosed with eGW (prevalence: 3.8%, 95% CI: 2.9–4.9). The highest prevalence was observed among 15–24 year-old women compared to women older than 25 years of age (7.2% vs 3.2%), with a trend significantly decreasing by increasing age (p-value < 0.001) and among women living in Southern Italy compared to those living in Central and Northern Italy (5.4% vs 2.5%, p = 0.003). The incidence was 3.0% (95% CI: 2.2–3.9). The estimated number of women with eGW among women aged 15–64 years in Italy in 2010 was approximately 69, 000. Conclusions: These data confirm the prevalence of eGW reported in a retrospective Italian study conducted among gynaecologists (Vittori et al. 2008), and stress the importance of clinical networks in investigating STI epidemiology, as well as promoting safe sex, implementing early diagnosis, treatment and prevention.